PENGENDALIAN PERSEDIAAN VAKSIN PADA DINAS KESEHATAN KABUPATEN HULU SUNGAI SELATAN - Marliza Noor Hayatie; Muhammad Aditya Aitama (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
In the case of vaccination in Indonesia, the problem that often occurs is the shortage of vaccine supplies in one area while in other areas there is a problem of excess vaccine supply which results in the accumulation of goods in warehouses. The purpose of this study is to determine which type of vaccine is more widely used in the community so that there is no excess or shortage of supplies. This study uses the Activity Based Costing (ABC) inventory control analysis method to determine which vaccine is more priority and which is more widely used in Hulu Sungai Selatan Regency. The type of data used in this study is quantitative data, namely data on entry and expenditure of vaccine supplies in 2021 at the Hulu Sungai Selatan District Health Office. The data source used is secondary data with documentation collection techniques. Based on the results of research using the ABC method, the stock of vaccine types that are more prioritized for use by the community is the type of group A vaccine, namely with 2 types of vaccines, namely Sinovac 1 ml and Sinovac 5 ml.